KEEFEKTIFAN PENGEMBANGAN MEDIA DIORAMA BERBASIS AUGMENTED REALITY DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD - Mahmudah, Nur Laila; Novialita Angga Wiratama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to create a diorama media based on augmented reality as a means to improve the learning outcomes of science in the food chain material for fifth grade students of Tunggul State Elementary School. As well as being used to overcome the minimal use of technology-based media and interactive media in Tunggul State Elementary School. The method used in this study is the development of R&D (Research and Development) which follows the ADDIE development model, this study specifically focuses on the